PERANAN PENDIDIKAN FORMAL DAN NON-FORMAL DALAM MENUNJANG KARIR SANTRI - Aghna Abdillah, Afiq (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to examine the role of formal and non-formal education in supporting the career development of Islamic boarding school (pesantren) students, based on the existing gap between the educational potential gained during their studies and their actual career achievements afterward. The research focuses on how the integration of these two educational pathways contributes to building the competence and work readiness of santri in facing a rapidly changing professional world. A descriptive qualitative approach was employed, using semi-structured interviews with current and former santri as the main data collection method. The findings reveal that formal education plays a crucial role in delivering general academic knowledge, providing legal certification (diplomas), and opening access to professional networks and structured skills. Meanwhile, non-formal education is seen as essential for character building, internalizing Islamic values, and fostering practical life skills. Although distinct in method and content, both forms of education complement each other in preparing santri to become skilled, adaptable, and competitive individuals. The study concludes that the integration of formal and non-formal education is vital in shaping santri who are not only religiously competent but also capable of navigating diverse career challenges in a sustainable manner